2020
DOI: 10.1186/s12889-020-8151-9
|View full text |Cite
|
Sign up to set email alerts
|

District level inequality in reproductive, maternal, neonatal and child health coverage in India

Abstract: Background: As India already missed maternal and child health related millennium development goals, the maternal and child health outcomes are a matter of concern to achieve sustainable development goals (SDGs). This study is focused to assess the gap in coverage and inequality of various reproductive, maternal, neonatal and child health (RMNCH) indicators in 640 districts of India, using data from most recent round of National Family Health Survey. Methods: A composite index named Coverage Gap Index (CGI) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Equal weighting schemes have been used successfully in creating indices related to infectious disease, 61 UHC 67 68 maternal and child health. 69 70 It has also been shown that the index created through principal component analysis is highly correlated with an index created through various weighting schemes and that arbitrarily defined weights did not make any difference to the composite coverage index. 60 71 In Mexico, a comparison of equal weights and weighting based on the total health gains yielded similar results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal weighting schemes have been used successfully in creating indices related to infectious disease, 61 UHC 67 68 maternal and child health. 69 70 It has also been shown that the index created through principal component analysis is highly correlated with an index created through various weighting schemes and that arbitrarily defined weights did not make any difference to the composite coverage index. 60 71 In Mexico, a comparison of equal weights and weighting based on the total health gains yielded similar results.…”
Section: Methodsmentioning
confidence: 99%
“…An equal weighting scheme was implemented for all the determinants as routinely applied. [67][68][69][70] Equal weighting schemes have shown to be equally robust; 56 58 60 61 65 71 however, the weighting scheme can be revised as more individual-level COVID-19 data with attributes become available in Kenya and other countries across Africa. This will allow a better definition of how the risks associated with different variables vary across different populations and settings.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…rural versus urban [28]. Studies in India also showed that the underprivileged groups like the nancially weak, poorly literate, or living in rural areas, had limited access to healthcare services, thus leading to poorer outcomes for health [29] [30]. Similar ndings were observed in the case of Pakistan and for the provinces except for Balochistan where the inequities continue to prevail in the same ratio during throughout the last decade.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, previous studies in the Indian context have found signi cant disparities in MCH service coverage and e ciency in service delivery across districts in India [51,52].…”
Section: Methodsmentioning
confidence: 96%